2022
DOI: 10.2991/apr.k.220503.001
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic and Kinetics Study of Copper Oxide on the Degradation of Methylene Blue Dye

Abstract: Methylene blue dyes in is widely used various industries in Indonesia, especially in the textile industry. Methylene blue in waters is toxic and difficult to degrade. One of the methods used is to overcome this problem is photocatalysis under visible light. CuO photocatalyst was prepared using an easy hydrothermal preparation using common autoclave at low temperature. The photocatalytic activity on methylene blue showed degradation up to 63.44%, with optimum pH 9 and the optimum irradiation time of 120 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A signifcant change in the absorbance intensity of the MB dye was obtained when the same amount of the MB dye was reacted with 1 mL of H 2 O 2 and 10 mg of ZnO NPs as shown in Figure 8(c). Tis indicated that the ZnO NPs have the catalytic properties to degrade the MB dye [39,54]. Te degradation studies were then investigated by varying MB dye concentration, pH, ZnO NP dosage, temperature, and interaction time [37][38][39].…”
Section: Xrd Analysismentioning
confidence: 99%
“…A signifcant change in the absorbance intensity of the MB dye was obtained when the same amount of the MB dye was reacted with 1 mL of H 2 O 2 and 10 mg of ZnO NPs as shown in Figure 8(c). Tis indicated that the ZnO NPs have the catalytic properties to degrade the MB dye [39,54]. Te degradation studies were then investigated by varying MB dye concentration, pH, ZnO NP dosage, temperature, and interaction time [37][38][39].…”
Section: Xrd Analysismentioning
confidence: 99%